Energy-savings technologies in civil-engineering - Lialiuk, O. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The modern state and development of energy-savings technologies is analyzed with determination of their specific contribution into civil engineering. The nomenclature of heatshield materials of world producers is presented. The criteria of economic efficiency are considered to choose the best energy-saving variant. The ways of solution of energy-saving problems are considered.